(untitled) (Salam International Academic Journal, 2025)
Linguistically, the term hijrah (migration) refers to leaving one’s homeland and relocating from one place to another. In Islamic jurisprudential terminology, hijrah traditionally refers to leaving a land of unbelief (Dar al-Kufr) and moving to a land of Islam (Dar al-Islam). It may also refer to departing from a land of injustice to a land of justice, or from a place of religious turmoil to one of safety, with the primary intention of preserving one’s faith. The phenomenon of leaving an Islamic country and migrating to non-Islamic countries, whether for temporary or permanent residence, represents a contemporary legal issue that requires clarification from the standpoint of Islamic law. The core focus of this research is to explore the Islamic jurisprudential position on migration to non-Islamic countries according to the views of classical and contemporary Islamic scholars. The importance of this issue stems from two key concerns: first, migration to non-Islamic countries poses a potential threat to the religious integrity of Muslim migrants; second, it presents a major challenge to the growth and development of Islamic nations, particularly Afghanistan. This research employs a library-based methodology, relying on the collection and analysis of scholarly opinions through inductive reasoning, evaluation, and analytical judgment. The findings reveal that the ruling of Islamic law on migration and residence in non-Islamic countries is highly dependent on specific contexts and circumstances. According to the predominant view among contemporary scholars of Islamic jurisprudence, if migration or residence in a non-Islamic country exposes the individual and their family to religious corruption and prevents the proper practice of Islamic rituals, then both temporary and permanent residence in such countries is prohibited (haram). If the migration is motivated solely by the pursuit of material well-being, comfort, or enjoyment, then it is considered strongly discouraged (makruh tahrimi) due to the high risk of spiritual harm and cultural assimilation. However, in cases of pressing necessity—such as inviting non-Muslims to Islam, seeking essential knowledge, accessing medical treatment, or fleeing from an oppressive ruler who threatens imprisonment or torture—such migration may be deemed obligatory (wajib) or recommended (sunnah). In ordinary circumstances, the ruling may range between permissibility (ibahah), discouragement (karahah), or conditional permissibility, depending on the individual’s situation.